Rediscovery of Rhacophorus yaoshanensis and Theloderma kwangsiensis at their type localities after five decades - Chen, Weicai; Liao, Xiaowen; Zhou, Shichu; Mo, Yunming; Huang, Yong (Zootaxa, 2018)
Rhacophorus yaoshanensis Liu & Hu, 1962 and Theloderma kwangsiensis Liu & Hu, 1962 were described by Liu & Hu (1962) based on two specimens and one specimen, respectively, from the Dayaoshan Ranges, Guangxi, China. Since these two species were described, no additional specimens have been collected from their type localities, presenting an issue for phylogenetic studies of the genera. Five decades later, we have rediscovered R. yaoshanensis and T. kwangsiensis from their type localities. In this paper, we re-describe the two species and conduct a preliminary assessment of their phylogenetic relationships using two mitochondrial DNA genes (12S and 16S rRNA). The results indicate with high support that R. yaoshanensis is closely related to Rhacophorus pinglongensis. Theloderma kwangsiensis is nested within Theloderma corticale, with only 0.0–0.6% pairwise divergence, a level typical of intraspecific variation. Based on both molecular and morphological analyses, we further confirm that T. kwangsiensis is a synonym of T. corticale. Shiwandashan National Nature Reserve, Guangxi Province, China, is a new record for T. corticale.